Development of a Discovery Learning Based Science E-Book Integrated with the Local Potential of Yogyakarta's Traditional Food Gudeg on the Topic of Elements, Compounds, and Mixtures - Assagaf*, Muhammad Dzulfikar; Widowati, Asri; Yunus, Sitti Rahma (Jurnal IPA & Pembelajaran IPA, 2025)
Science learning in schools is often dominated by monotonous and less contextual material delivery, resulting in low student enthusiasm and passive participation. Limited engagement, poor collaboration, and the lack of learning resources that incorporate local potential present significant challenges. One proposed solution is the development of an e-book based on the discovery learning model, integrated with local potential specifically Yogyakartas traditional food, gudeg on the topic of elements, compounds, and mixtures. This study aims to develop a science e-book based on the discovery learning model integrated with the local potential of yogyakarta's traditional food, gudeg, on the topic of elements, compounds, and mixtures. The development model used is addie, limited to the analyze, design, develop, and evaluate stages. Data were collected using validation instruments by subject matter experts and media experts, as well as practicality and readability questionnaires administered to science teachers and students. Data were analyzed using the coefficients of reproducibility (CR) and scalability (CS), along with average score calculations. The results showed that the developed e-book met the validity criteria with CR 90% and CS 60% as assessed by both experts. The practicality assessment by science teachers fell into the high to very high category, while the readability test by students yielded an average score of 3.26, categorized as very good. These results indicate that the developed e-book is valid, practical, and feasible for use in science learning